A Qualitative Study exploring the Impact of Infertility on Iranian Women's Sexual Health - Zahra Daneshfar; Shahideh Jahanian; Fazlollah Ahmadi; Giti Ozgoli; Anoshirvan Kazemnejad (Mashhad University of Medical Sciences, 2023)
Background & aim:  Infertility has serious implications on psychological and social well-being as well as the sexual life. Considering that sexual health is an essential element of human health, the present study was performed to explore the experiences of Iranian infertile women regarding their sexual health. Methods: This qualitative study was conducted using conventional content analysis (Lundman and Graneheim's approach) in Tehran, Iran from November to March 2018. Twenty infertile women (aged 25-42 years old with various reasons for infertility), who were selected purposefully, participated in this study. The data were collected through in-depth semi-structured interviews All interviews were tape-recorded and transcribed verbatim. Guba and Lincoln's criteria including credibility, transferability, confirmability, and dependability were applied to achieve trustworthiness. Results: Three themes emerged from the data analysis including 1) Impact of the process of diagnosis and treatment on women's sexuality 2) Psychological, behavioral, interpersonal and economic factors influencing sexual health, and 3) cultural and religious norms affecting sexual life. Conclusion: Infertile women's sexual health is influenced by the process of diagnosis and treatment; psychological reactions to infertility, economic, personal, and cultural-belief system.